PERBANDINGAN PENGUASAAN KONSEP SISWA MELALUI PENDEKATAN KETERAMPILAN PROSES SAINS DAN PENDEKATAN PEMBELAJARAN KONSEP - Destiana -; Nengah Maharta; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2013)
This research aims to know average mastery students in Learning Skills through sika Internet process of Science (KPS) and the concept of Learning approach (PK). Experimental design on this research uses Kuasi Experimental Design with Posttest-Only type Control Design. Data analysis techniques mastery PK using an average score of an average mastery of concepts and hypothesis testing using the test for Independent Samples T Test, While the concept of mastery KPS data analysis using data based on the learning process of observation and hypothesis testing using the test for Independent Samples T Test.Based on concept mastery test obtained average mastery students in experimental class 1 (KPS approach) se be sar 90 (due diligence). On the experimental class 2 (PK approach) gained an average mastery students exactly sar 80 (completely). Based on the results of calculations known drift score concept mastery students in classes of KPS 79,32% (completely), while the average grade PK, known to score students ' mastery of 65,60% (completely).These results indicate that KPS approach more effectively used as an effort to promote mastery of the concepts students in learning.Keywords: Science Process Skills Approach (KPS), Concept Learning Approach (PK), mastery of the concepts students.